Stochastic Peer-To-Peer Energy Trading with Price and Incentive Mechanism - Mishra M.; Singh A.; Misra R.K.; Singh D. (My University, 2025)
With the emerging role of the Peer-To-peer (P2P) energy sharing concept in effectively utilising renewable energy resources, the need for a suitable incentivising/pricing method is also increasing. In this work, a cooperative game is formulated in a community of buildings where a community battery energy storage system (CBESS) acts as a player along with other buildings. With the help of generalised Nash bargaining, the problem is formulated and minimised in a decentralised way using ADMM. 'Hong's 2m point estimate method' is used for stochastic modelling renewable generation uncertainties. Suitable incentives are decided to motivate the players to engage in this game of P2P energy sharing. Along with the incentives, prices per unit of energy shared are also calculated. When compared, both methods give almost the same results. © 2022 IEEE.